The Economic Effect of Remittances in Conflict Affected Countries - Kumičák, Juraj; Křečková Kroupová, Zuzana, 1972-; Villaverde Castro, José; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2017)
The remittance flows have played an important role in the economies of developing and least developed countries in the past 30 years. The fragility of these countries to any type of adverse economic shocks, natural disasters or military conflicts have made the remittance flows one of the major cash flows which can help to alleviate the disturbances and volatilities of income constraints. In this master thesis, we are focusing onto the relations between the remittance flows and conflicts and how significant are variables influencing the remittance flows in time periods of military conflicts. We are using the panel data for 46 countries from all over the world in time period of 1985-2016, which were, or still are affected by the adverse economic shock caused by a military conflict. We find that the remittance flows can increase in presence of adverse economic shock caused by the onset or military conflict while controlling for the Official Development Assistance flows and the development of banking sector.
Vedoucí práce: Zuzana Křečková Kroupová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: economics of globalisation and european integration [obor dipl. práce]; diplomové práce; master's theses